Survey of Barley and wheat Parasitic Microflora in the Republic of Macedonia (Journal of Agriculture and Plant Sciences, 2013)
The continuous observation of the health condition of cereal crops in the Republic of Macedonia has enabled us to undertake this detailed review of parasitic microfl ora on wheat and barley. During the last six years (2004-2009), the most important and the most widespread diseases of wheat and barley have been the following:Cochliobolus sativus - causal agent of spot leaf blotch of barley (Hordeum vulgare)Ustilago nuda - causal agent of loose smut of barleyPyrenophora graminea - causal agent of leaf stripe on barleyRhynchosporium secalis - causal agent of barley scald Tapesia yallundae - causal agent of “eyespot” of barleyМycosphaerella graminicola – causal agent of Septoria tritici blotch of wheatAll of these diseases cause damage to the health of the plants as well as the quality of the yield, and all of them will be the subject of study in the following seasons.